Improving Student Learning Outcomes in Social Studies Learning Using Quantum Teaching Model in Elementary School - Hennika, Sandra Aulia; Disman, Disman (International Conference on Elementary Education, 2021)
This research is motivated by teachers who do not prepare lesson plans, are less able to create meaningful experiences for students, rarely provide opportunities for students to name material, do not provide opportunities for students to demonstrate student knowledge, and rarely give acknowledgment of student participation. As a result, the learning outcomes obtained by students were low. The purpose of this study was to describe the increase in student learning outcomes in social studies learning using the quantum teaching model in grade 4 of Bandar Buat Elementary School. The research method used was classroom action research. The results showed that, a) Lesson plan, cycle I was 78.6% with good qualifications and cycle II was 89.3% with very good qualifications, b) the results of the implementation of teacher and student activities, cycle I was 76.6% with good qualifications and cycle II is 87.5% with very good qualifications. c) student learning outcomes, cycle I obtained an average score of 74.4% with sufficient qualifications, and cycle II an average score of 82.7% with good qualifications. Thus, the quantum teaching model can improve student learning outcomes in social studies learning in grade 4 of Bandar Buat Elementary School.